2017
DOI: 10.1038/srep41958
|View full text |Cite
|
Sign up to set email alerts
|

Virtual touch tissue imaging and quantification (VTIQ) in the evaluation of thyroid nodules: the associated factors leading to misdiagnosis

Abstract: To evaluate the associated factors leading to misdiagnosis with VTIQ for differentiation between benign from malignant thyroid nodules (TNs). The study included 238 benign TNs and 150 malignant TNs. Conventional ultrasound (US) features and VTIQ parameters were obtained and compared with the reference standard of histopathological and/or cytological results. Binary logistic regression analysis was performed to select independent variables leading to misdiagnosis. The maximum shear wave speed (SWS) (SWS-max), m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 36 publications
2
22
0
Order By: Relevance
“…A total of 643 publications were identified upon systematic review of the literature, of which 42 remained after removing duplicates, literature reviews, studies not related to Kwak’s TIRADS and those written in a language other than English or German. Analysis of abstracts and full texts allowed isolation of six original studies that assessed the K-TIRADS scale proposed by Kwak, consistent with the meta-analysis objectives [ 20 25 ] (Fig. 1 ).…”
Section: Resultsmentioning
confidence: 61%
See 1 more Smart Citation
“…A total of 643 publications were identified upon systematic review of the literature, of which 42 remained after removing duplicates, literature reviews, studies not related to Kwak’s TIRADS and those written in a language other than English or German. Analysis of abstracts and full texts allowed isolation of six original studies that assessed the K-TIRADS scale proposed by Kwak, consistent with the meta-analysis objectives [ 20 25 ] (Fig. 1 ).…”
Section: Resultsmentioning
confidence: 61%
“…In the study by Zhang and Sun, ultrasound check was also taken into account for TIRADS 2 category lesions with initial benign cytology [ 21 , 25 ] (Table 1 ). The cut-off value in four studies was category 4a/4b [ 20 , 22 24 ] and in last two studies category 3/4a [ 21 , 25 ]. The funnel graph for analysed studies was asymmetrical, which may suggest publication bias (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Elastography cannot be performed on nodules with a calcified shell because the sound waves cannot penetrate the calcifications [13]. Intralesional coarse calcifications may bias the stiffness of the lesion, as can peripheral calcifications [11,86]. A partially cystic character is expected to alter nodule elasticity, although the direction of this expected effect is not known [13,14].…”
Section: Influencing Factorsmentioning
confidence: 99%
“…Therefore, an association between SWS and pathological processes of the tumors was not able to be established. However, this was not the aim of the present study, as previous studies have demonstrated that the difference in the stiffness is associated with tissue reorganization, particularly fibrosis and necrosis ( 2 , 47 , 52 ). Secondly, the results of these experiments are not directly applicable to human liver cancer tissues: The present tumor model was implanted under the skin of the nude mice.…”
Section: Discussionmentioning
confidence: 86%
“…The SWS mean values were markedly correlated with the tumor growth curve induced by NET-1 siRNA. However, it was also noted that comparison of the SWS max values between the two treated groups did not indicate a significant difference, which may be attributed to the location of the 7 ROIs that avoided the cystic, calcified and necrotic areas, thereby affecting the result ( 36 , 47 ). Furthermore, SWS mean achieved the highest diagnostic performance compared with the other measured values.…”
Section: Discussionmentioning
confidence: 95%